2009
DOI: 10.1093/bja/aep299
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy as an index of brain and tissue oxygenation

Abstract: Continuous real-time monitoring of the adequacy of cerebral perfusion can provide important therapeutic information in a variety of clinical settings. The current clinical availability of several non-invasive near-infrared spectroscopy (NIRS)-based cerebral oximetry devices represents a potentially important development for the detection of cerebral ischaemia. In addition, a number of preliminary studies have reported on the application of cerebral oximetry sensors to other tissue beds including splanchnic, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
559
1
23

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 738 publications
(590 citation statements)
references
References 86 publications
7
559
1
23
Order By: Relevance
“…In addition, prior work has indicated that meaningful alterations in cerebral saturation can be determined in this manner, for example, pre-and post-carotid cross-clamping with carotid endarterectomy. 10,11 Lastly, establishing an a priori agreed upon baseline permits true comparisons across the maximal number of studies. 7 In these experiments, we show desaturations using the same type of cerebral oximeter (i.e., CasMed FORE-SIGHT) used by Hemmerling et al 7 This oximeter claims absolute cerebral oximetry, not just documentation of trends.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, prior work has indicated that meaningful alterations in cerebral saturation can be determined in this manner, for example, pre-and post-carotid cross-clamping with carotid endarterectomy. 10,11 Lastly, establishing an a priori agreed upon baseline permits true comparisons across the maximal number of studies. 7 In these experiments, we show desaturations using the same type of cerebral oximeter (i.e., CasMed FORE-SIGHT) used by Hemmerling et al 7 This oximeter claims absolute cerebral oximetry, not just documentation of trends.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the mean decrease in cerebral saturation from baseline in this study is similar to that which correlated to the increased morbidity seen with carotid cross-clamping. 10 While not equivalent to an ipsilateral occlusion of blood flow to a cerebral hemisphere, the magnitude of the cerebral desaturation suggests that it is important to have a better understanding of the problem.…”
Section: Discussionmentioning
confidence: 99%
“…A 20-G catheter was placed in the radial artery for obtaining blood gas analysis and monitoring invasive arterial blood pressure (ABP). Adhesive electrodes oximetry (INVOS TM Cerebral/ Somatic Oximeter, Somanetics TM , Troy, MI, USA) [5] for monitoring the regional cerebral oxygenation were stuck symmetrically on the forehead, high above the eyebrows to avoid positioning over sinus cavities. Patients were then placed in a prone position on a Jackson surgical table and the procedure was performed under general anesthesia in the usual fashion [6].…”
Section: Methodsmentioning
confidence: 99%
“…The review by Murkin and Arango 12 suggests that a [ 12% decrease in cerebral saturation is ''a reliable, sensitive, and relatively specific threshold for brain ischemia secondary to internal carotid artery clamping''. Our work suggests that the Fore-Sight cerebral oximeter may provide very early notification of intraoperative cerebral compromise as assessed by a large SctO 2 difference following cross-clamping of the carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have been both positive and negative regarding the value of cerebral oximetry to aid management during CEA (see reviews). 12,13 A newer cerebral oximeter -the Fore-Sight monitor is now commercially available. This monitor is deemed to be superior to devices previously available and claims to be an absolute measure of cerebral oxygenation.…”
Section: Résumémentioning
confidence: 99%